The International Social Organisation of Educational Research in Europe: reviewing the European Educational Research Association as an example – facts and questions - Gretler, Armin (European Educational Research Journal, 2007)
Armin Gretler passed away on 6 October 2005. Armin was a founder member of the EERA and served on its Council, representing Switzerland. He was a sociologist and founding director of the Swiss Coordination Centre for Research in Education in 1971. He remained Director until retiring in 1999. Prior to that he had been working as a consultant for UNESCO (Paris) and the Bureau International du Travail (Geneva). He was amongst others a founding member of the Swiss Society for Research in Education (SSRE), the European Educational Research Association and other international associations. He published in different areas of education policy, including migration, teacher education research, and the place of education research in the social sciences. In the early 1990s, Armin was asked to convene a meeting of national educational research associations in Aarau in Switzerland, in order to establish the EERA. Armin was a great supporter of the European Education Research Association. In this article, originally titled ‚Fakten und Fragen zur internationalen sozialen Organisation der Bildungsforschung in Europa am Beispiel der European Educational Research Association’, he describes the early days of the Association. It is important to be reminded about the early desires of its founding members for a European association and its priorities. (Of course, some of the information about the national associations, in particular their membership figures, is no longer valid today.)
Keywords: utilisation des recherches